Production of Hepatitis B Viral Antigens and Antibodies using Phage Display Technology for the Development of a Diagnostic Test - Tan, Geok Hun (2006)
Hepatitis B is one of the most common infectious diseases in the world. It is caused by the hepatitis B virus (HBV) which is estimated to infect more than one third of the world's population and there are about 400 million carriers of HBV worldwide. The infection can now be prevented through immunization with a vaccine based on the surface antigen (HBsAg) produced in yeast by genetic engineering. In order to provide additional means to control the disease, rapid, easier and cheaper diagnostic assay have been developed using phage display technology in these studies. From the present studies, bacteriophage T7 was employed to display the immune dominant region of S-HBsAg, amino acid residues 1 1 1-1 56, on the exterior of the phage particles. The expressed immune dominant region of S-HBsAg remained antigenic and it was displayed on the coat protein of the recombinant phage particle, T7-HBsAglll-lj6, which has the potential to be used as an immunological reagent for the detection of anti-HBsAg antibody in human serum samples at as low as 0.25 mIUIml. In addition, the hsion phage also applied on dotblot for detection of anti-HBsAg antibody. However, the sensitivity of this assay is low as compared to ELISA method. A phage heptapeptide random library was used to identify peptide ligands that interact with HBsAg. From the third round of panning, 75% of phages screened carried the peptide sequence C-ETGAKPH-C which is the most frequently identified phage clones in this round. The phage clone was characterized and a cyclic synthetic peptide bearing the identical peptide sequence was synthesized. The phage was able to compete with anti-HBsAg monoclonal antibody as well as the synthetic peptide for the binding site on HBsAg. The optimum pH and temperature for phage binding was around 4 to 8 and 4"C, respectively. An equilibrium binding assay in solution showed that the phage binds tightly to HBsAg with a relative dissociation constant (KC') of 2.9 f 0.9 nM, illustrating that the phage bearing ETGAKPH has the potential to be used as a diagnostic reagent for detecting HBsAg in human sera. As a preliminary effort to study the detection of HBcAg in the serum samples, single chain variable fragment (scfv) of anti-HBcAg antibody library was constructed by fusion to gpIII protein of bacteriophage M13, which allows for the display of the fusion protein (scfv) at the tip of the filament. Truncated HBcAg was inoculated into female BalbIC mice before the antibody and spleen cells were harvested for the construction of library. Multiple reactions of PCR were carried out, and the size of the antibody library was 2.18 x lo7 cfidml. This library was further panned against HBcAg to get the specific phage clone that interacts with HBcAg. The phage clone with higher absorbance value was further rescued by helper phage M13K07, and the phagemid was digested to determine the insert of scfi. In this study, a phage-ELISA assay was established and the minimum amount of HBcAg that can be detected was about 10 ng with 1.0 x 1 012 pfidml of purified fusion phage. This hsion phage scfv showed a promising result for the detection of HBcAg in the human treated serum samples. In conclusion, development of phage-ELISA for the detection of anti-HBsAg antibody, HBsAg and HBcAg based on phage display can be an alternative choice to reduce the cost of detection kits. This study also provides a model in the development of diagnostic test for the detection of other biological samples based upon phage display technology.